Parkinson’s disease managing reversible neurodegeneration - Hinz M (Dove Medical Press, 2016)
Marty Hinz,1 Alvin Stein,2 Ted Cole,3 Beth McDougall,4 Mark Westaway5 1Clinical Research, NeuroResearch Clinics, Inc., Cape Coral, FL, 2Stein Orthopedic Associates, Plantation, FL, 3Cole Center for Healing, Cincinnati, OH, 4CLEARCenter of Health, Mill Valley, CA, USA; 5Four Pillars Health, Brendale, QLD, Australia Abstract: Traditionally, the Parkinson’s disease (PD) symptom course has been classified as an irreversible progressive neurodegenerative disease. This paper documents 29 PD and treatment-induced systemic depletion etiologies which cause and/or exacerbate the seven novel primary relative nutritional deficiencies associated with PD. These reversible relative nutritional deficiencies (RNDs) may facilitate and accelerate irreversible progressive neurodegeneration, while other reversible RNDs may induce previously undocumented reversible pseudo-neurodegeneration that is hiding in plain sight since the symptoms are identical to the symptoms being experienced by the PD patient. Documented herein is a novel nutritional approach for reversible processes management which may slow or halt irreversible progressive neurodegenerative disease and correct reversible RNDs whose symptoms are identical to the patient’s PD symptoms. Keywords: Parkinson’s disease, L-dopa, carbidopa, B6, neurodegeneration